FAMILY HEALTH CARE COSTS OF LIFESTYLE DISEASES - V. VIJAYA LAKSHMI, N. PAVANI, D. RATNA KUMARI and (The Journal of Research, PJTSAU, 2017)
Health care has emerged as one of the most progressive and target sector in India, with a GDP spend of 8 per cent in 2012 up from 5.5 per cent in 2009. Health care in India is at an inflection point now and is poised to grow up to US$ 280 billion by2020 which is a growth of over ten times since 2005 (Source: Indian Hospital Services Market Outlook).